Development of an Exe-Learning-based Mathematics E-module on Sequences and Series - Putri Mediana Anggraini; Yesi Gusmania; Fitrah Amelia; Bayu Nadya Kusuma (Program Studi Tadris Matematika IAIN Salatiga, 2023)
This study aims to produce Exe-Learning-based mathematics e-modules on sequences and series material for grade XI Vocational High School (SMK) that are valid, effective, and practical. This research is development research (RD) with the ADDIE development model. The research subjects were math teachers and class XI students at SMK Putra Jaya Centre. The research instruments were expert assessment sheets, posttest questions, and teacher and student response assessment sheets. Based on the results, the e-module is categorized as very valid with an average score for content eligibility was 3.41, presentation feasibility was 3.60 and language was 3.50. Furthermore, the assessment of media experts obtained an average score on the aspect of graphic feasibility of 3.61 and media feasibility of 3.50. Testing the effectiveness of the e-module based on the results of the students' posttest obtained classical completeness results of 91% in the very effective category, while the teacher and student response questionnaire for the practicality of the e-module was 90% and 88% in the practical category. Thus, the Exe-Learning-based mathematics e-module on sequences and series material for grade XI Vocational High School students that has been developed is declared valid, effective, and practical.